The Commensal Microbe Veillonella as a Marker for Response to an FGF19 Analog in NASH. Issue 1 (11th December 2020) - Loomba, Rohit; Ling, Lei; Dinh, Duy M.; DePaoli, Alex M.; Lieu, Hsiao D.; Harrison, Stephen A.; Sanyal, Arun J.
Abstract : Background and Aims: The composition of the human gut microbiota is linked to health and disease, and knowledge of the impact of therapeutics on the microbiota is essential to decipher their biological roles and to gain new mechanistic insights. Here we report the effect of aldafermin, an analog of the gut hormone FGF19, versus placebo on the gut microbiota in a prospective, phase 2 study in patients with NASH. Approach and Results: A total of 176 patients with biopsy‐confirmed nonalcoholic steatohepatitis (NASH) (nonalcoholic fatty liver disease activity score ≥ 4), fibrosis (F1‐F3 by NASH Clinical Research Network criteria), and elevated liver fat content (≥ 8% by magnetic resonance imaging–proton density fat fraction) received 0.3 mg (n = 23), 1 mg (n = 49), 3 mg (n = 49), and 6 mg (n = 28) aldafermin or placebo (n = 27) for 12 weeks. Stool samples were collected on day 1 and week 12 and profiled using 16S ribosomal RNA gene sequencing; 122 patients had paired stool microbiome profiles at both day 1 and week 12. Overall, the state of the gut microbial community was distinctly stable in patients treated with aldafermin, with all major phyla and genera unaltered during therapy. Patients treated with aldafermin showed a significant, dose‐dependent enrichment in the rare genus Veillonella, a commensal microbe known to have lactate‐degrading and performance‐enhancing properties, which correlated with changes in serum bile acid profile. Conclusions: Veillonella may be a bile acid–sensitive bacteria whose enrichment is enabled by aldafermin‐mediated suppression of bile acid synthesis and, in particular, decreases in toxic bile acids. This study provides an integrated analysis of gut microbiome, serum bile acid metabolome, imaging, and histological measurements in clinical trials testing aldafermin for NASH. Our results provide a better understanding of the intricacies of microbiome–host interactions (clinicaltrials.gov trial No. NCT02443116).